111 The Prevalence of Asthma in Canadian Kindergarten Children and its Association with their Developmental Health: A Population-Level Cross-Sectional Study. (29th October 2021) - Schneeweiss, Michelle; Reid-Westoby, Caroline; Hu, George; Pottruff, Molly; Janus, Magdalena
Abstract: Primary Subject area: Epidemiology Background: Asthma, the most common chronic illness affecting Canadian youth, can profoundly and adversely impact a child's quality of life. Previous studies have shown a diagnosis of asthma can influence a child's physical and socio-emotional functioning. Current data on asthma prevalence rates among Canadian children is scarce, and it is still unclear how this diagnosis impacts their development at school entry. Objectives: The goals of the current study were to 1) examine the prevalence of teacher-reported asthma in Canadian kindergarten children, and 2) investigate the association between asthma and children's concurrent developmental health. Design/Methods: A cross sectional, population-level study of kindergarten children diagnosed with asthma as reported on the Early Development Instrument (EDI), was carried out in Canada from 2010-2015. Children's developmental health in kindergarten was measured with the EDI. This 103-item questionnaire is completed by teachers for their students aged 4-6 years and covers demographic information, as well as five different domains of development. Descriptive statistics were examined for children with and without asthma. The level of statistical significance was adjusted using a Bonferroni correction to account for multiple hypothesis testing. The chi-square and one-way ANOVA statistics, as well as effect sizes (Cramer's V, and eta squared) were reported for all descriptive analyses. Results: 958 children (0.002% of the final analytical sample) were identified as having a teacher-reported diagnosis of asthma. Compared to their peers, children with asthma were significantly more likely to: be male (68.2% vs 51.2%); have a special needs designation (19.0% vs 3.6%); have a functional impairment (53.5% vs 15.9%); be identified by their teachers as needing further developmental assessment (32.3% vs. 13.1%); and miss, on average, 3 more days of school than their peers (9.44 vs. 6.71). They were also more likely to fall below a vulnerability threshold on one or more of the developmental domains (55.9% vs. 28.8%, Figure 1). Conclusion: It is likely that the EDI captures only severe cases of asthma, as parents are more likely to disclose their child's illness to teachers if it may influence their ability to function in a classroom. As such, children with asthma, especially those with severe forms, may require additional support. A partnership in which physicians provide preventative care, and teachers provide academic and classroom assistance, may help to ensure the optimal development of children with asthma, and close gaps between them and their peers.